Concrete ice abrasion rig and wear measurements - Shamsutdinova, G. (author); Rike, P.B. (author); Hendriks, M.A.N. (author); Jacobsen, S. (author) (2015)
The wear of concrete material due to ice movement is a challenge for offshore and coastal structures. Concrete surfaces exposed to moving ice are subjected to wear at various rates depending on concrete and ice properties. At NTNU, Department of Structural Engineering, concrete ice abrasion phenomena are studied both theoretically and experimentally. This paper describes the accelerated concrete ice abrasion rig which was comprehensively improved recently. Together with surface measurement equipment, it is believed that the new experimental facility will give new input for understanding of the underlying mechanisms of ice abrasion. Structural Engineering Civil Engineering and Geosciences